UNDERSTANDING LIPOMA OF OCCIPITAL REGION - A DETAILED CASE ANALYSIS” - swatee agarwal (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2026)
Maxillofacial surgeons rarely encounter scalp lipomas in their clinical practice. These may be post traumatic or associated with other factors. Mostly of mesenchymal origin , only 13% originate in head and neck region. We ,present here a post traumatic scalp lipoma in occipital region which was considerably large in size. The report highlights the current management and treatment modalities for their management and role of maxillofacial surgeons in treating such cases.